Expanding Studio Boundaries: Navigating Tensions in Multidisciplinary Collaboration within and beyond the Higher Education Design Studio. (5th November 2020) - McAra, Marianne; Ross, Kirsty
Abstract: In this article the authors set out and critically reflect upon an innovative pedagogical approach to delivering studio‐based learning – drawing on the 'Collaborative Futures' project. Collaborative Futures is a live project premised on a futures‐focused design brief written with an external partner. In previous iterations of the project, partners have included Hitachi and the Royal Bank of Scotland. Each year this project brings together a team of students in their final year on the Masters European Design programme to collaborate with a group of early career design graduates. Between 2019 and 2020, the Collaborative Futures project worked with Glasgow City Council's Centre for Civic Innovation to explore and prototype citizen‐centred scenarios surrounding data experiences set in the context of Glasgow 2030. Throughout the project the student‐graduate team engaged in multidisciplinary collaboration within and beyond the boundaries of the higher education studio context, working with civic, academic and design professionals, public and third sector organisations, and members of the public. The authors reflect on the design process; theoretically unpack the cross‐cultural, studio‐based collaboration that took place; and discuss the complex challenges that emerged and the meditating role design artefacts played. The insights presented in the article have value for design educators seeking new approaches to designing and delivering studio‐based design learning that fosters creative, multidisciplinary communities of practice and collaborative capacity‐building for design students in a professional setting.